The changes of microplastics' behavior in adsorption and anaerobic digestion of waste activated sludge induced by hydrothermal pretreatment. (1st August 2022) - Jiang, Chao; Ni, Bing-Jie; Zheng, Xiaowei; Lu, Bei; Chen, Zheng; Gao, Yang; Zhang, Yalei; Zhang, Shicheng; Luo, Gang
Highlights: MPs' specific surface area increased while relative crystallinity decreased after HTP. Poor thermal stability groups of MPs were converted to ketone or carboxyl groups. HTP resulted in blocking the adsorption of a variety of MPs for pollutants. HTP enhanced the inhibitory effect of MPs on AD by accelerating TOC release. Leachate of MPs reduced the abundance of vital anaerobes. Abstract: Waste activated sludge (WAS) contains high concentrations of microplastics (MPs), which could serve as vectors of various organic pollutants and heavy metals, causing synergistic transportation and pollution. The application of combined hydrothermal pretreatment (HTP) and anaerobic digestion (AD) has raised growing concerns since the low-temperature hydrothermal treatment could enhance the biogas production of WAS. However, the changes in physicochemical properties, adsorption performances, and effects on AD of MPs by HTP have not been studied. The study used three typical MPs in WAS, and it was found that the HTP (170°C & 30min) increased MPs' specific surface area and carbonyl index (CI) while decreasing the relative crystallinity. The adsorption capacity to Cd increased through the carbonylation for polyethylene microplastic (PE-MP) and polystyrene microplastic (PS-MP) while decreasing by the dechlorination for polyvinyl chloride microplastic (PVC-MP). Meanwhile, increased hydrophilicity reduced the adsorption capacities of all three typical MPs for ofloxacin. The above results indicated that the HTP could be worth blocking the adsorption of polar MPs for polar pollutants. For the pristine MPs, only PVC-MP at the highest concentration (0.5 g kg −1 VS) significantly ( p  < 0.05) reduced methane production by 16.2 ± 3.3% of WAS without the HTP. However, the HTP resulted in significant ( p  < 0.05) inhibition of methane production of WAS at high concentrations of PE-MP and PVC-MP (e.g., 0.1 and 0.5 g kg −1 VS), which was due to the acceleration of the released toxic plastic additives (dibutyl phthalate, dimethyl phthalate, and bisphenol-A). Microbial analysis showed the abundances of vital anaerobes, such as acid-producing bacteria ( Acetoanerrobium and Mesotoga ), proteolytic bacteria ( Proteiniborus ), and methanogens ( Methanosaeta ) clearly decreased with the PE-MP and PVC-MP after the HTP, which might result in the decreased methane production. The study provided deep-insight of MPs' behaviors during the combined HTP-AD process. Graphical abstract: Image, graphical abstract